CONDUCTIVITY ANALYSIS OF CU/N-GRAPHENE AND NI/N-GRAPHENE AS ELECTRODES ON PRIMARY BATTERY ANODES - Simanjuntak, Crystina; Siburian, Rikson; Jiamin, Amanda (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2024)
This study used a modified Hummer method to synthesize Graphene and nitrogen dopant to produce N-Graphene. Cu/N-Graphene and Ni/N-Graphene electrodes were each made using the impregnation method. Conductivity analysis of graphene, N-graphene, Cu/N-Graphene, and Ni/N-Graphene was carried out using a multimeter. The conductivity data of Cu/N-Graphene (83.16 µS/cm) and Ni/N-Graphene (85.67 µS/cm) produced were higher than commercial battery anodes (26 µS/cm). These data prove that N-graphene can improve the performance of Cu/N-Graphene and Ni/N-Graphene on primary battery anodes and can be used as an alternative anode on primary battery anodes.